Gigahertz Electromagnetic Structures via Direct Ink Writing for Radio‐Frequency Oscillator and Transmitter Applications. Issue 15 (15th February 2017) - Zhou, Nanjia; Liu, Chengye; Lewis, Jennifer A.; Ham, Donhee
Abstract : Radio‐frequency (RF) electronics, which combine passive electromagnetic devices and active transistors to generate and process gigahertz (GHz) signals, provide a critical basis of ever‐pervasive wireless networks. While transistors are best realized by top‐down fabrication, relatively larger electromagnetic passives are within the reach of printing techniques. Here, direct writing of viscoelastic silver‐nanoparticle inks is used to produce a broad array of RF passives operating up to 45 GHz. These include lumped devices such as inductors and capacitors, and wave‐based devices such as transmission lines, their resonant networks, and antennas. Moreover, to demonstrate the utility of these printed RF passive structures in active RF electronic circuits, they are combined with discrete transistors to fabricate GHz self‐sustained oscillators and synchronized oscillator arrays that provide RF references, and wireless transmitters clocked by the oscillators. This work demonstrates the synergy of direct ink writing and RF electronics for wireless applications. Abstract : Gigahertz electromagnetic structures are fabricated for radio‐frequency (RF) oscillator and transmitter applications. Direct ink writing of silver‐nanoparticle inks enables precise control over their 3D structure and function. The printed electromagnetic structures and their use in RF oscillators and transmitters are characterized.